ANALYSIS OF DIRECTIVE ILLOCUTIONARY ACT UTTERED BY CHARACTERS IN THE TWILIGHT SAGA: "BREAKING DAWN PART 2" - Kezia Tiwa; Sanerita T. Olii; Fivy Andries (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The aims of the research are to find out the types of directive illocutionary acts in “The Twilight: Breaking Dawn Part 2”, and to interpret and explain the contextual meaning of those directives. This research is a qualitative research. The steps that the researchers have taken in order to collect the data are watching the movie, marking the types of directives that identified as asking, commanding, requesting, ordering, forbidding, advising, and suggesting, and interpreting the meaning of those directives. The data are categorized based on Vanderveken’s classifications. The three steps proposed by Miles and Huberman for data analyses are used in this study: data reduction, data display, and data verification/conclusion. The findings of this study reveal a total of 51 speech acts uttered by the characters in the movie The Twilight Saga: Breaking Dawn Part 2.This research is suggested to be a reference for the readers and the other researchers in order to learning and interpreting the directive illocutionry act in movies or the other literature works.